Low-cooling-rate freezing in biomolecular cryo-electron microscopy for recovery of initial frames. (6th September 2021) - Wu, Chunling; Shi, Huigang; Zhu, Dongjie; Fan, Kelong; Zhang, Xinzheng
Abstract: Resolutions of per-frame reconstructions for various samples frozen at different cooling rates. ( a ) Resolutions of per-frame reconstructions of various samples frozen by lowering the cooling rate. The green lines are for apo-ferritin (rhombus), glutamate dehydrogenase (GDH; square) and virus-like particles (VLP; triangle) collected in the pink region marked in Fig. 1a. The red lines are for apo-ferritin (rhombus), GDH (square) and aldolase (triangle) frozen at −110 °C. Aldolase was frozen on an Au grid covered with a holey NiTi film (regular triangles), and also on a Cu grid covered with a holey carbon film (inverted triangle). The grey line shows the resolutions of downloaded per-frame reconstructions (EMD-11210) of DNA protection protein during starvation (DPS). ( b ) Resolutions of per-frame reconstructions of GDH datasets using a cooling-rate gradient. The green dataset was collected for a standard frozen sample formed at the highest cooling rate, the blue dataset was collected in the light-blue region in Fig. 1a, and the red dataset was collected in the pink region in Fig. 1a. Abstract: When biological samples are first exposed to electrons in cryo-electron microcopy (cryo-EM), proteins exhibit a rapid 'burst' phase of beam-induced motion that cannot be corrected with software. This lowers the quality of the initial frames, which are the least damaged by the electrons. Hence, they are commonly excluded or down-weighted during data processing, reducing the undamaged signal and the resolution in the reconstruction. By decreasing the cooling rate during sample preparation, either with a cooling-rate gradient or by increasing the freezing temperature, we show that the quality of the initial frames for various protein and virus samples can be recovered. Incorporation of the initial frames in the reconstruction increases the resolution by an amount equivalent to using 60% more data. Moreover, these frames preserve the high-quality cryo-EM densities of radiation-sensitive residues, which is often damaged or very weak in canonical three-dimensional reconstruction. The improved freezing conditions can be easily achieved using existing devices and enhance the overall quality of cryo-EM structures.